Development of Interactive E-Modules Using Conceptual Change Text Strategies to Reduce Student Misconceptions on The Material Colligative Properties of Solutions - Sabila, Sabrina Aji; Sukarmin, Sukarmin (Jurnal Pendidikan dan Pembelajaran Kimia, 2023)
The purpose of this study is to obtain interactive e-module products using conceptual change text strategies to reduce student misconceptions on the material colligative properties of solutions that are suitable for use. The colligative nature of solutions is a chemical material that is considered difficult because it is abstract and complex, causing students to find it difficult to understand the material. Learners who have difficulty in understanding the material's colligative properties of solutions can lead to misconceptions. To reduce misconceptions, an effort is needed, namely using a conceptual change text strategy packaged in the form of electronic learning media such as interactive e-modules. This study was prepared using research and development (R&D) research methods development model by Borg and Gall with descriptive analysis based on mode and shift misconceptions. Interactive e-module using conceptual change text strategy to reduce students' misconceptions on the material colligative properties of solutions are declared feasible based on content validity and construct, practicality and effectiveness. The validity of the content and construct obtained 4 or valid modes, practicality with a percentage of response questionnaire sheets of 95.8% or very practical and the percentage of observation sheets of student activities of 92.94% or very practical, and effectiveness in terms of the results of shifting misconceptions obtained by 87.36%. The results showed that the interactive e-module using the conceptual change text strategy to reduce students' misconceptions on the material colligative properties of the solution was declared feasible for useDOI: 10.23960/jppk.v12.i3.2023.03